ANALISIS KEBUTUHAN PENGEMBANGAN INSTRUMEN DIAGNOSTIK BENTUK THREE TIER MULTIPLE CHOICE BILANGAN CACAH BAGI PESERTA DIDIK SEKOLAH DASAR BERBASIS EDUCAPLAY - Aprianti, Desi; Wahyu Lestari, Deni Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the need for the development of a diagnostic instrumentin the form of three tier multiple choice on the material of whole numbers forelementary school students integrated with Educaplay interactive media. Thediagnostic instrument developed is expected to be able to identify misconceptionsmore accurately and provide meaningful feedback. The research method uses aqualitative descriptive approach with data collection techniques through literaturestudies, teacher interviews, and questionnaires. The results of the study show thatteachers really need an instrument that can reveal the reasons behind students'answers and use interactive media such as Educaplay to increase student interestand involvement. Recommendations for instrument development include creatingquestions with three tiers (answers, reasons, beliefs) and implementation throughthe Educaplay platform.